Analysis of Service Quality Toward Customer Satisfaction in the Legend Coffee Yogyakarta - Luthfy Kasim (Fakultas Ekonomi dan Bisnis Islam, 2021)
The service quality in the institution is the main purpose of Sleman Regency Social Service. To carry out a high quality institution, it needs a process to be better considered from several aspects of customer satisfaction. The importance of special attention to customer satisfaction is also based on the institution awareness in the increasing of the competition threat that will be tighter with the same government agencies. The objective of this study are 1). To determine the effect of tangibles toward customer satisfaction at Sleman Regency Social Service 2). To determine the effect of reliability toward customer satisfaction at Sleman Regency Social Service 3). To determine the effect of responsiveness toward customer satisfaction at Sleman Regency Social Service 4). To determine the effect of assurance toward customer satisfaction at Sleman Regency Social Service. 5). To determine the effect of empathy toward customer satisfaction at Sleman Regency Social Service 6). To determine the simultaneous effect of tangibles, reliability, responsiveness, assurance and empathy toward customer satisfaction at Sleman Regency Social Service. The results of the analysis are discussed more detail in the data analysis. This research is conducted based on existing methods, which refers to the five dimensions of SERVQUAL, that discuss the service toward customer satisfaction at Sleman Regency Social Service. Significant service quality dimensions are the responsiveness with a significance value is 0.003 and Empathy with a significance value is 0.048 indicating smaller than 0.05. While the attributes of service quality dimensions that obtained an insignificant satisfaction rating are Tangibles with a significance value is 0.236, Reliability with a significance value is 0.238 and Assurance with a significance value is 0.127.